2021
DOI: 10.1080/10409238.2021.1979460
|View full text |Cite
|
Sign up to set email alerts
|

The AAA+ superfamily: a review of the structural and mechanistic principles of these molecular machines

Abstract: ATPases associated with diverse cellular activities (AAAþ proteins) are a superfamily of proteins found throughout all domains of life. The hallmark of this family is a conserved AAAþ domain responsible for a diverse range of cellular activities. Typically, AAAþ proteins transduce chemical energy from the hydrolysis of ATP into mechanical energy through conformational change, which can drive a variety of biological processes. AAAþ proteins operate in a variety of cellular contexts with diverse functions includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 284 publications
(389 reference statements)
1
74
0
Order By: Relevance
“…Notably, hexameric AAA+ ATPases specific for nucleic acid as well as protein translocation share a conserved asymmetric spiral organization around their cognate substrates and are furthermore believed to share a similar translocation rate per hydrolysed ATP molecule 20,38,54 . Similarly, the pulling of DNA, RNA and protein substrates is thought to be powered by a common sequential nucleotide cycle 21,39,44,49,50 . On the basis of their shared geometrical and mechanistic properties, our findings suggest that the majority of ring-shaped AAA+ ATPase translocases may function as molecular levers that efficiently convert a concerted wave of conformational changes associated with their nucleotide cycles into a defined lift-height of their central pores, as a common basic mechanism to facilitate substrate translocation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, hexameric AAA+ ATPases specific for nucleic acid as well as protein translocation share a conserved asymmetric spiral organization around their cognate substrates and are furthermore believed to share a similar translocation rate per hydrolysed ATP molecule 20,38,54 . Similarly, the pulling of DNA, RNA and protein substrates is thought to be powered by a common sequential nucleotide cycle 21,39,44,49,50 . On the basis of their shared geometrical and mechanistic properties, our findings suggest that the majority of ring-shaped AAA+ ATPase translocases may function as molecular levers that efficiently convert a concerted wave of conformational changes associated with their nucleotide cycles into a defined lift-height of their central pores, as a common basic mechanism to facilitate substrate translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous biochemical and structural evidence suggests that branch migration is facilitated by a tripartite complex: RuvA tetramers assemble around the Holliday junction crossover to provide structural guidance for DNA separation and rewinding and are flanked by two hexameric RuvB AAA+ ATPases that together fuel the translocation of the newly emerged recombined DNA [12][13][14][15][16][17][18][19] . Furthermore, these studies demonstrated that domain III of RuvA (RuvA D3 ) binds to the presensor-1 β-hairpin of RuvB, a distinguishing feature of the PS1 insert superclade 20,21 , regulates branch migration and increases ATPase activity of the RuvB motor 22,23 . Moreover, the ability for cross-species hetero-complementation established the existence of a robust and conserved mechanism of the RuvA-and RuvB AAA+-coordinated action at the Holliday junction 24,25 .…”
mentioning
confidence: 99%
“…AAA + ATPases are present in all eukaryotes, acting as macromolecular machines powered by the energy derived from ATP hydrolysis to induce conformational changes in their substrates (White & Lauring, 2007). While their core ATPase module is structurally highly conserved (Erzberger & Berger, 2006; Khan et al ., 2021), the remaining regions of these proteins are quite variable and show great diversity, which accounts for their multiple functions and roles (Snider et al ., 2008). AAA + ATPases are molecular chaperones that affect the fate of other proteins by facilitating protein folding and unfolding, the assembly or disassembly of protein complexes, aiding membrane fusion events, unwinding of DNA, altering DNA–protein complexes or participating in protein degradation (Ogura & Wilkinson, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…AaFRAT1 is a member of a tandemly duplicated cluster of AAA + ATPases and has a weak flowering phenotype in A. thaliana Aa_G106560 encodes a protein of 496 amino acids from the AAA + superfamily of ATPases, which usually present three conserved domains, namely Walker A, Walker B and an Arginine finger (Erzberger & Berger, 2006;Wendler et al, 2012;Khan et al, 2021). The A. thaliana genome contains c. 140 AAA + ATPases, none of which has been reported to be involved in flowering time (Ogura & Wilkinson, 2001).…”
Section: New Phytologistmentioning
confidence: 99%
“…7 Cytoplasmic dynein belongs to the AAA+ superfamily of proteins. 13 There are nine subfamilies of dynein consisting of two cytoplasmic and seven axonemal dyneins. 12 A homodimer that is composed of two heavy chains (DHC, encoded by DYNC1H), two light intermediate chains (DLIC, encoded by DYNC1LI), four intermediate chains (DIC, encoded by DYNC1I), and six light chains (DLC, encoded by DYNLT1 or TcTex-1, DYNLL1 or LC8, and DYNLRB) that contribute to dynein's ~1.4 MDa molecular weight.…”
Section: Introductionmentioning
confidence: 99%